The classic sound of Rudy Van Gelder. An investigation of the recording techniques used to create the iconic blue note sound - Mathebula, Mthokozisi (College of Music, 2025)
The Blue Note Sound, a “classic sound” created by Rudy Van Gelder in his Hackensack home during the 1950s, is characterized by the techniques he employed in his recordings, imparting warmth, clarity, and precision. This dissertation explores and evaluates Van Gelder's techniques, their effectiveness, and their potential application in the modern era. This work aims to raise awareness and offers insights and comparisons regarding the unique aesthetics of recordings in jazz. This dissertation takes a self-reflexive approach as it explicitly examines the Blue Note Sound and its effectiveness. To support this, data was collected through critical listening analysis and a comparison of literature, articles, and media captions. The techniques used were based on exploration and experimentation, leading to the creation of the Blue Note Sound, which became the signature sound of the Blue Note Records label in the 1950s and 1960s. This label featured some of the most iconic jazz records of all time. The dissertation aims to demonstrate a clear understanding of the creation of the Blue Note Sound, the evolution of jazz recording sound, and the aesthetics based on specific techniques.